Desorption and re-adsorption of PAHS on aircraft soot surface - Lan, Nguyen Mai (Vietnam Journal of Earth Sciences, 2020)
Polycyclic Aromatic Hydrocarbons (PAHs) in aircraft soot are capable to distribute in the gas phase and particulate phase in chemical transformations in the atmosphere. The desorption of PAHs from the soot surface is a preliminary step in the study of the reactivity of particulate PAHs. The desorption kinetics of PAHs are measured from soot samples to determine desorption rate constants for different PAHs as a function of temperature and the binding energies between PAHs and soot. The kinetics of degradation of particulate PAHs were studied in the flow reactor. The soot samples previously deposited on a Pyrex tube are introduced into the reactor along its axis and the concentrations of PAHs adsorbed on soot are determined by the High-Performance Liquid Chromatography (HPLC) as a function of the desorption time. The results show a correlation between the size of PAHs and the thermodynamics of desorption: with the PAHs have the same number of carbon atoms, their energies of desorption are very similar and increase with this number. The activation energies EA and the number of carbon atoms in PAHs have a linear correlation. It is consistent with the additivity of the laws Van der Waals. The similarity between the activation energies of desorption of PAHs and the corresponding sublimation enthalpies is consistent with the similarity between the graphitic structure of soot and the structure of PAHs.